Aggregate Gradation Influence on Marshall and Stiffness of AC-WC Mixtures - I Wayan Putra Jayantara Jayantara; Wenny Herdianti; I Gede Wyana Lokantara; Anggiat Daniel Anderson Munthe; Rizky Simanjuntak (Universitas Pendidikan Nasional, 2026)
Aggregate gradation plays an important role in determining the performance of asphalt mixtures used in road pavement structures. Numerous studies have investigated the influence of aggregate gradation on Marshall characteristics and volumetric properties of asphalt mixtures. However, limited studies have examined the combined effect of aggregate gradation variations within the specification limits on both Marshall characteristics and stiffness performance of AC-WC mixtures. In addition, the influence of proportional gradation variations across the specification envelope has not been widely discussed. Therefore, this study aims to investigate the influence of aggregate gradation variations within the specification limits of Asphalt Concrete Wearing Course (AC-WC) on optimum asphalt content, Marshall characteristics, and mixture stiffness. Five aggregate gradation variations were prepared using the proportional method based on gradation limits. Laboratory tests were conducted using Marshall testing and Indirect Tensile Stiffness Modulus (ITSM) to evaluate mixture performance. The results show that aggregate gradation significantly affects the optimum asphalt content and mechanical characteristics of the mixture. Finer aggregate gradation increases the aggregate surface area and requires higher asphalt content. The optimum asphalt content for different gradation variations ranged from 5.7% to 6.3%. In addition, finer gradation produced lower air voids (VIM) and resulted in higher Marshall stability and mixture stiffness. These findings indicate that aggregate gradation has a significant influence on the volumetric and mechanical properties of AC-WC mixtures.